Last Mile Delivery Collaboration Proposal to Achieve Delivery Cost Efficiency in E-Commerce - Sutandi Sutandi; Yuli Evitha; I Nyoman Purnaya (Jurnal Logistik Indonesia, 2021)
The E-commerce market in Indonesia has grown significantly in the last couple of years and proved by the emerging of key players in the e-commerce field. This phenomenon affects the improvement of the logistic sector which is one of the backbones of E-Commerce. According to the data, logistic sectors contribute 24% to Indonesia’s gross domestic product (GDP) and 25% to logistic business income which is acquired from delivery services of E-Commerce goods (PwC, 2019). On the other hand, Indonesia is an archipelago country consisting of 17.500 islands with a width of 1.905-million kilometers square. With the geographical condition of Indonesia, it becomes a challenge for E-Commerce logistic industry practitioners. To overcome these problems, corporations should take actions such as system improvement and also collaboration to decrease distribution facility establishment cost, transportation facility establishment, cost-saving seen from distribution distances, total manpower, and lastly is improvement and maintenance system in each logistic corporation. To ensure success in collaboration, corporations should show commitment to the customers by giving the best and cheapest services in order to guarantee the success of the collaboration. Other things which can be done to achieve the success are by showing collaboration commitment to other E-Commerce logistic service providers by showing the willingness to share information and data about each other and lastly, the existence of collaborator whose or which responsible for connecting both parties, whether it is third party or information collaborating system.